The impact of the universities closure on physical activity and academic performance in physical education in university students during the COVID-19 pandemic - Aleksander Yu. Osipov; Tatyana I. Ratmanskaya; Elena A. Zemba; Vladimir Potop; Mikhail D. Kudryavtsev; Roman S. Nagovitsyn (Physical Education of Students, 2021)
Background and Study Aim. Physical activity (PA) is regarded as a critical component of a healthy lifestyle and disease prevention. Different constraints placed upon social interaction and public spaces due to COVID-19 could decrease PA and academic performance in physical education (PE) in student population. The purpose of the research was to assess overall and sport/fitness PA level and academic performance in PE in a sample of university students pre- to post-cancellation of face-to-face PE classes due to the COVID-19 pandemic.